1986
DOI: 10.1083/jcb.103.6.2145
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ionophore A23187 as a regulator of gene expression in mammalian cells.

Abstract: Abstract. The calcium ionophore A23187 can reversibly induce the expression of two glucose-regulated genes, p3C5 and p4A3. This induction requires a continuous presence of the ionophore for over 2 h. Although extracellular Ca 2+ is important for the optimal effect of A23187, it is not necessary for the induction, since a similar response with a lower magnitude can be triggered in cells cultured in low Ca 2+ medium buffered with EGTA. Both the basal and induced levels of p3C5 and p4A3 transcripts can be modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…Several studies implicate HSPs as part of a generalized stress response. Induction of HSP mRNAs after thermal, ischemic, or traumatic injury of the nervous system has been demonstrated for several of the axonally synthesized HSPs that we have identified (Resendez et al, 1986;Lowenstein et al, 1991;Tedeschi and Ciavarra, 1997;Costigan et al, 1998;Liu et al, 1998;Yu et al, 1999;Mengesdorf et al, 2001;Hori et al, 2002). The HSPs are best characterized as molecular chaperones that can facilitate protein folding and formation of heteromolecular complexes and direct proteins to subcellular regions and organelles (Welch, 1992;Ohtsuka and Suzuki, 2000).…”
Section: Axonal Synthesis Of Heat Shock Proteinsmentioning
confidence: 99%
“…Several studies implicate HSPs as part of a generalized stress response. Induction of HSP mRNAs after thermal, ischemic, or traumatic injury of the nervous system has been demonstrated for several of the axonally synthesized HSPs that we have identified (Resendez et al, 1986;Lowenstein et al, 1991;Tedeschi and Ciavarra, 1997;Costigan et al, 1998;Liu et al, 1998;Yu et al, 1999;Mengesdorf et al, 2001;Hori et al, 2002). The HSPs are best characterized as molecular chaperones that can facilitate protein folding and formation of heteromolecular complexes and direct proteins to subcellular regions and organelles (Welch, 1992;Ohtsuka and Suzuki, 2000).…”
Section: Axonal Synthesis Of Heat Shock Proteinsmentioning
confidence: 99%
“…Despite the sequence similarity between the mammalian glucose-regulated core sequence and the S. cerevisiae UPRE, no single element in this promoter region appears necessary and sufficient to mediate transcriptional induction as described for the UPRE in yeast cells. In addition, although transcriptional activation in response to conditions that disrupt protein folding in the ER correlates with changes in activities of protein kinases and phosphatases (Resendez et al 1986;Koong et al 1994a;Cao et al 1995;Chen et al 1998), a signaling molecule that responds to unfolded protein in the ER to induce transcription of the ER protein chaperone genes has not been identified. In this report we describe the identification and characterization of a human gene product that is equivalent to Ire1p of S. cerevisiae and functions as a proximal sensor for the UPR in mammalian cells.…”
mentioning
confidence: 99%
“…First, the transcriptional activation of the GRP78 gene is sensitive to the protein synthesis inhibitor cycloheximide (8,20), whereas the induction of the heat-inducible HSP70 gene does not require de novo protein synthesis. In fact, it has been demonstrated that the heat shock regulatory factor can bind to the heat shock element in the presence of cycloheximide (26).…”
mentioning
confidence: 99%
“…To facilitate the search for cellular factors which interact with the DNA regulatory domain, we utilized the HeLa cell system, which can be grown in suspension to provide high yields of cellular extracts. We have shown previously that GRP78 transcripts can be detected in a variety of mammalian cell lines (20). Since the focus of this study was on the utilization of the human HeLa S3 cell line as a source of functional protein extracts, we first investigated the expression of the endogenous GRP78 gene in these cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation